2021
DOI: 10.1021/acssuschemeng.1c02558
|View full text |Cite
|
Sign up to set email alerts
|

Poly(hydroxyurethane) Adhesives and Coatings: State-of-the-Art and Future Directions

Abstract: Polyurethane (PU) adhesives and coatings are widely used to fabricate high-quality materials due to their excellent properties and their versatile nature, which stems from the wide range of commercially available polyisocyanate and polyol precursors. This polymer family has traditionally been used in a wide range of adhesive applications including the bonding of footwear soles, bonding of wood (flooring) to concrete (subflooring), in the automotive industry for adhering different car parts, and in rotor blades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 101 publications
0
58
0
Order By: Relevance
“…Today, poly(hydroxyurethane)s (PHU)s, synthesized by polyaddition of cyclic carbonates and amines, are considered as greener alternatives to conventional polyurethanes ( Figure ). [ 119–122 ] PHUs bear additional primary or secondary hydroxyl groups, in comparison to classic polyurethanes, that faster bond exchanges and enable the preparation of vitrimers. [ 123 ]…”
Section: Transcarbamoylation Reactionsmentioning
confidence: 99%
“…Today, poly(hydroxyurethane)s (PHU)s, synthesized by polyaddition of cyclic carbonates and amines, are considered as greener alternatives to conventional polyurethanes ( Figure ). [ 119–122 ] PHUs bear additional primary or secondary hydroxyl groups, in comparison to classic polyurethanes, that faster bond exchanges and enable the preparation of vitrimers. [ 123 ]…”
Section: Transcarbamoylation Reactionsmentioning
confidence: 99%
“… 2 , 5 Examples of biobased precursors include glycols, natural oils, and fatty acids used in resin production 6 , 7 and agricultural byproducts such as starch and lignin compounds. 3 , 8 10 However, in the quest to find and identify renewable raw materials for use in coatings and adhesives, epoxy materials are lagging behind compared to other polymers (e.g., biobased polyurethanes and polyesters) 5 , 11 to be released as commercially available products. For instance, one-to-one replacement of petroleum-based products with epoxy biobased products is not yet possible.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, some promising results towards new adhesive and coating technologies have emerged. Gomez-Lopez et al [16] recently reported an overview on poly(hydroxyurethane) polymers derived from biobased poly(cyclic carbonate)s and synthetic diamines. The polycarbonate precursor can react with both aliphatic and cyclic amines, and with highly reactive melamines, such as hexamethoxy methyl melamine (HMMM), to produce solvent-based and solvent-free thermosets.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, some promising results towards new adhesive and coating technologies have emerged. Gomez‐Lopez et al [16] . recently reported an overview on poly(hydroxyurethane) polymers derived from biobased poly(cyclic carbonate)s and synthetic diamines.…”
Section: Introductionmentioning
confidence: 99%